Effect of ZN Suplementation on Blood Glucose Levels and Insulin Resistance in Diabetes Mellitus - Sefti Atletika Asiani; Gaga Irawan Nugraha; Sunarjati Sudigdoadi (Syntax Corporation Indonesia, 2021)
Diabetes mellitus (DM) is a metabolic disorder characterized by high levels of glucose in the blood. Micromineral levels are related to the mechanism of glucose homeostasis. The abnormal zinc levels can be risk factors for DM. Improvement of micro-mineral levels can improve blood sugar levels. This study aimed to review the effects of zinc supplementation on blood glucose levels and insulin resistance. This study showed that DM was associated with low zinc levels in body serum. Zinc supplementation reduced fasting blood glucose, hemoglobin A1c levels, and insulin resistance in rat model DM and human researchs. It occurs in many types of Zn supplements. Differences in results may be due to differences in the characteristics of the subjects, doses, and periods of administration. Zn can be used for nutritional therapy in DM by considering the dose and period of supplementation, and patient characteristics to get optimal results